THE EFFECT OF PASAK BUMI ROOTS TOWARDS BLOOD GLUCOSE LEVEL IN GLUCOSE-LOADED MICE - Fransisca Fransisca; Gracia Easter Kalangi; Damiana Sapta Candrasari; Phebe Hendra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2018)
The aim of this research is to evaluate the effect of pasak bumi roots (Eurycoma longifolia Jack) towards the blood glucose level in glucose-loaded mice. The blood glucose-lowering effects were tested using Oral Glucose Tolerance Test (OGTT) method. The mice were given with infusion of pasak bumi roots at the doses of 0.83; 1.67; 3.33 g/kgBW and methanol extract of pasak bumi roots at the doses of 102; 210; 420 mg/kgBW. All treatments were conducted orally, 30 minutes before the administration of glucose (2 g/kgBW). The blood glucose levels were measured at 0 minute before the administration of glucose and at 15, 30, 60, 90, and 120 minutes after the administration of glucose. Blood samples were obtained through the mice tails vena lateralis using glucometer. The blood glucose levels result which were obtained at the 0 until 120 minutes were calculated to obtain AUC. AUV values of each treatment group were analyzed statistically. Based on the results of the research, it can be concluded that the methanol extract of pasak bumi roots has blood glucose-lowering effect at the doses of 210 and 420 mg/kgBW, but infusion of pasak bumi roots does not have effects on lowering the blood glucose level in the glucose-loaded mice.